Incorporation of bentazone with Exserohilum rostratum for controlling Cyperus iria - Kundat, Franklin Ragai; Loo, Hoong Shen; Ahmed, Osumanu Haruna (Science Publications, 2010)
Problem statement: Various methods are used to counter the population of Cyperus iria in rice fields and among the most common method are chemical approaches. Chemical control methods are preferred by rice farmers due to their efficacy, speed, ease of storage and affordable cost. The concern of chemical herbicides is on its effects on the environment. Less attention had been given to biological control methods. Limitations such as host specificity, formulations and storage requirements are some of the obstacles that have to be overcome before implementation. Although it is environmentally friendly, a total shift from chemical control methods to biological seems unreasonable. Therefore incorporation of biological control with reduced chemical herbicides is expected to produce a better and sustainable control of weeds. Approach: A study was conducted to determine the potential of using Exserohilum rostratum as a biocontrol agent (incorporated with chemical herbicide, bentazone) to control Cyperus iria. The biocontrol agent (E. rostratum) was confirmed to be pathogenic to C. iria by applying Koch's postulates. Preliminary laboratory experiments were carried out to ensure the interactions within the mixture was not inhibitory. Results: Bentazone was confirmed to be compatible with E. rostratum with an ED50 value of 22064570.0 µgai mL-1. In order to determine the efficacy of the incorporations, several mixtures were tested in a greenhouse environment. It was found that the mixtures of E. rostratum (106 spores mL-1) with bentazone (0.4 kgai ha-1) was significantly a better control of Cyperus iria compared to the usage of bentazone alone (0.4 kgai ha-1) and spores alone (106 spores mL-1). It was significantly more effective than the mixture of RBD palm oil (10%), Tween 80 (5%) and spores (106 spores mL-1) which acted as the conventional bioherbicide approach. Synergistic effects were exhibited with 50% less herbicide concentrations from the recommended rates. The mixture exhibited 50% disease severity in 3.5 days compare to bentazone alone which requires 4.9 days and the conventional bioherbicide mixture was relatively less effective requiring 4.7 days. The mixture of spores alone required 7.6 days to achieve 50% disease severity. This suggests that the mixture can save 50% of the cost on bentazone while providing a faster control. Conclusion: The incorporations were confirmed to be successful in providing a better and environmentally friendlier method than the conventional methods of weed control.